A Response to Social, Economic and Political Conditions During the Soekarno Government Period; Cempakadilaga Manuscript of Mama Sempur - Ma'mun, Titin Nurhayati; Hazmirullah,; Afidah, Ida (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the Cempakadilaga manuscript, the work of KH Tubagus Ahmad Bakri (1839-1975), famous ulama who is known as Mama Sempur in Purwakarta, West Java.In reality, the manuscript was completed in 1959. However, the objective of study in this article is the published text, with Mama Sempur’s approval, in 1962. The manuscript, which was written using the Sundanese Pegon script (Sundanese), contains five articles and one faidah.In it, Mama Sempur explained the importance of farming, running an illegitimate business, the obligation to maintain good relations between people, the obligation to serve the government even though it is unjust, and how it is better to prevent harm over bringing benefit. In the faidah, Mama Sempur invited the society to return to the Shafi’i school. The results showed that the Cempakadilaga manuscript was presented as a response to the Indonesian social, economic and political conditions, especially in the late 1950s to the 1960s. At present, Indonesia experiences deterioration in various aspects of life.